2020
DOI: 10.1111/nph.17073
|View full text |Cite
|
Sign up to set email alerts
|

From pollen dispersal to plant diversification: genetic consequences of pollination mode

Abstract: Summary Pollinators influence patterns of plant speciation, and one intuitive hypothesis is that pollinators affect rates of plant diversification through their effects on pollen dispersal. By specifying mating events and pollen flow across the landscape, distinct types of pollinators may cause different opportunities for allopatric speciation. This pollen dispersal‐dependent speciation hypothesis predicts that pollination mode has effects on the spatial context of mating events that scale up to impact populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 88 publications
(121 reference statements)
3
54
0
Order By: Relevance
“…Because reproductive traits directly influence mating patterns (Wessinger, 2021) and fitness (and therefore are under strong selection), they are well‐suited to studying how selection and gene flow generate species divergence (Nosil and Crespi, 2004; Rice and Pfennig, 2010). Among angiosperms, flowers exhibit a stunning diversity of floral forms, colors, scents, and mechanisms by which they shape the reproductive success and genic exchange of plants (Armbruster, 2014).…”
mentioning
confidence: 99%
“…Because reproductive traits directly influence mating patterns (Wessinger, 2021) and fitness (and therefore are under strong selection), they are well‐suited to studying how selection and gene flow generate species divergence (Nosil and Crespi, 2004; Rice and Pfennig, 2010). Among angiosperms, flowers exhibit a stunning diversity of floral forms, colors, scents, and mechanisms by which they shape the reproductive success and genic exchange of plants (Armbruster, 2014).…”
mentioning
confidence: 99%
“…The morphological (e.g., large‐bodied) and behavioral traits of these generalist bird pollinators facilitates their access to more distant resources, supporting their existence in fragmented landscapes (Hagen et al., 2012 ; Yates et al., 2007 ). These traits decrease the risk of failure in the delivery of pollinator services (Wessinger, 2020 ). However, as habitat loss intensifies, particularly in urban ecosystems, the distance between remnants increases, reducing bird mobility because of their high resource requirements (Hagen et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…More than 349,000 animal species forage on flowers worldwide, with over 87% of angiosperms relying on animal‐mediated pollination for sexual reproduction and genetic recombination (Kearns & Inouye, 1997; Ollerton, 2017; Ollerton et al., 2011). The behavior of pollinators during pollination has fundamental consequences for plant mating and determines the maximum frequency and diversity of mating opportunities (Harder & Barrett, 1996; Minnaar et al., 2019; Wessinger, 2020). There is ample evidence that habitat loss, alteration, and disturbance can negatively impact pollinators and plant–pollinator interactions (Bennett et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5S-IGS data to study complex history of wind-pollinated trees The permeability of species boundaries sets apart wind-and insect-pollinated, common tree genera. A recent study on genetic consequences of pollination mode (Wessinger, 2021) showed that wind pollination leads to reduced population genetic structure. For example, in one insect-and one wind-pollinated species of Chamaedorea (Arecaceae) in Mexico, the wind-pollinated species showed less isolation by distance as compared to the insect-pollinated species; the same was true in two common shrubs co-occurring in Mediterranean scrub, Pistacia lentiscus (wind-pollinated) and Myrtus communis (insect-pollinated).…”
Section: Discussionmentioning
confidence: 99%